CRISPR-Cas9-based approaches for genetic analysis and epistatic interaction studies in Coxiella burnetii - Samuel Steiner; Craig R. Roy (mSphere)
ABSTRACT Coxiella burnetii is an obligate intracellular bacterial pathogen that replicates to high numbers in an acidified lysosome-derived vacuole. Intracellular replication requires the Dot/Icm type IVB secretion system, which translocates over 100 different effector proteins into the host cell. Screens employing random transposon mutagenesis have identified several C. burnetii effectors that play an important role in intracellular replication; however, the difficulty in conducting directed mutagenesis has been a barrier to the systematic analysis of effector mutants and to the construction of double mutants to assess epistatic interactions between effectors. Here, two CRISPR-Cas9 technology-based approaches were developed to study C. burnetii phenotypes resulting from targeted gene disruptions. CRISPRi was used to silence gene expression and demonstrated that silencing of effectors or Dot/Icm system components resulted in phenotypes similar to those of transposon insertion mutants. A CRISPR-Cas9-mediated cytosine base editing protocol was developed to generate targeted loss-of-function mutants through the introduction of premature stop codons into C. burnetii genes. Cytosine base editing successfully generated double mutants in a single step. A double mutant deficient in both cig57 and cig2 had a robust and additive intracellular replication defect when compared to either single mutant, which is consistent with Cig57 and Cig2 functioning in independent pathways that both contribute to a vacuole that supports C. burnetii replication. Thus, CRISPR-Cas9-based technologies expand the genetic toolbox for C. burnetii and will facilitate genetic studies aimed at investigating the mechanisms this pathogen uses to replicate inside host cells.IMPORTANCEUnderstanding the genetic mechanisms that enable C. burnetii to replicate in mammalian host cells has been hampered by the difficulty in making directed mutations. Here, a reliable and efficient system for generating targeted loss-of-function mutations in C. burnetii using a CRISPR-Cas9-assisted base editing approach is described. This technology was applied to make double mutants in C. burnetii that enabled the genetic analysis of two genes that play independent roles in promoting the formation of vacuoles that support intracellular replication. This advance will accelerate the discovery of mechanisms important for C. burnetii host infection and disease.